IL-35 inhibits cell pyroptosis and attenuates cell injury in TNF-α-induced bronchial epithelial cells via p38 MAPK signaling pathway. Issue 1 (1st January 2022) - Wang, Yanbo; Yu, Yanling; Yu, Wanjing; Bian, Xun; Gong, Linxia
ABSTRACT: Asthma is a chronic inflammatory disease of the airways, and IL-35 has been found to be involved in the pathogenesis of inflammatory diseases by mediating the inhibition of effector T cells. But the role of IL-35 on cell pyroptosis, which frequently occurs in inflammatory diseases, has not been elucidated. Therefore, the present study used a TNF-α-induced bronchial epithelial cell injury model to investigate the mechanism of IL-35 action on cell pyroptosis and asthma injury. The effects of IL-35 on cell activity, inflammatory factor levels, cell barrier damage and cell pyroptosis-related proteins were examined by CCK-8, ELISA, lucifer yellow permeability and Western blotting assay, respectively. Subsequently, following the activation of p38 MAPK signaling pathway by adding p38 agonist, the effect of IL-35 on TNF-α-induced bronchial epithelial cell injury was investigated. The results showed that IL-35 reduced TNF-α-induced cell injury, decreased inflammatory factors, improved cell permeability, and inhibited cell pyroptosis. More importantly, the effect of IL-35 on injured cells was reversed after p38 MAPK pathway was activated. In summary, IL-35 inhibited p38 MAPK pathway to suppress cell pyroptosis and thereby reduce asthma injury.